Cortex-specific transcriptome profiling reveals upregulation of interferon-regulated genes after deeper cerebral hypoperfusion in mice - Zhang, Zengyu; Guo, Zimin; Tu, Zhilan; Yang, Hualan; Li, Chao; Hu, Mengting; Zhang, Yuan; Jin, Pengpeng; Hou, Shuangxing (Frontiers in Physiology, 2023)
Background Chronic cerebral hypoperfusion (CCH) is commonly accompanied by brain injury and glial activation. In addition to white matter lesions, the intensity of CCH greatly affects the degree of gray matter damage. However, little is understood about the underlying molecular mechanisms related to cortical lesions and glial activation following hypoperfusion. Efforts to investigate the relationship between neuropathological alternations and gene expression changes support a role for identifying novel molecular pathways by transcriptomic mechanisms. Methods Chronic cerebral ischemic injury model was induced by the bilateral carotid artery stenosis (BCAS) using 0.16/0.18mm microcoils. Cerebral blood flow (CBF) was evaluated using laser speckle contrast imaging (LSCI) system. Spatial learning and memory were assessed by Morris water maze test. Histological changes were evaluated by Hematoxylin staining. Microglial activation and neuronal loss were further examined by immunofluorescence staining. Cortex-specific gene expression profiling analysis was performed in sham and BCAS mice, and then validated by quantitative RT-PCR and immunohistochemistry (IHC). Results In our study, compared with the sham group, the right hemisphere CBF of BCAS mice decreased to 69% and the cognitive function became impaired at 4 weeks postoperation. Besides, the BCAS mice displayed profound gray matter damage, including atrophy and thinning of the cortex, accompanied by neuronal loss and increased activated microglia. Gene set enrichment analysis (GSEA) revealed that hypoperfusion-induced up-regulated genes were significantly enriched in the pathways of interferon (IFN)-regulated signaling along with neuroinflammation signaling. Ingenuity pathway analysis (IPA) predicted the importance of type I IFN signaling in regulating the CCH gene network. The obtained RNA-seq data were validated by qRT-PCR in cerebral cortex, showing consistency with the RNA-seq results. Also, IHC staining revealed elevated expression of IFN-inducible protein in cerebral cortex following BCAS-hypoperfusion. Conclusion Overall, the activation of IFN-mediated signaling enhanced our understanding of the neuroimmune responses induced by CCH. The up-regulation of IFN-regulated genes (IRGs) might exert a critical impact on the progression of cerebral hypoperfusion. Our improved understanding of cortex-specific transcriptional profiles will be helpful to explore potential targets for CCH.